Oxford dictionary of phrasal verbs - Cowie, A P (Oxford New York : Oxford University Press, 1993)
This new edition has benfited from generous help and advice from several sources. We woud particularly like to thank Oxford University Press for kindly allowing us to draw on the Oxford Corpus fo the English Languaje for numreous up-ti date items and examples.
Contents Structure of entries in the dictionary Abbreviations and symbols used in the dictionary Alphabetical list of particles and prepostions
Keywords: ENCICLOPEDIA Y DICCIONARIOS; DICCIONARIO DE INGLÉS